Transitioning from face-to-face classes to emergency remote learning - Vargas Barquero, Vivian (2022)
Abstract The COVID-19 pandemic forced higher education institutions to pivot their traditional face-to-face teaching to emergency remote teaching (ERT), causing a shift in delivery modalities. Recent studies have described ERT's existing experiences as an emerging transitioning methodological alternative to comply with the social distancing and safety guidelines stipulated globally. This research study merges data from two sources in a convergent parallel mixed method design. Thus, the study presents a systematization of the action plan undergone by the faculty authorities of Universidad Nacional of Costa Rica and a follow-up trace analysis of newcomer's experiences in the Bachelor major in English Teaching as a Foreign Language at the school of Literature and Language Sciences (ELCL, Spanish initials) during the first term of 2020. Results evince the students' experience in tech possibilities, electronic device ownership, and healthy, economic, social, or physical learning setting issues. Lastly, the researchers propose an empathetic design thinking further research study to determine where to integrate technology at the BA TEFL major.   Keywords: COVID-19 pandemic, face-to-face teaching, emergency remote teaching, newcomer students' experiences, higher education